EXPLORING STUDENTS‘ VIEWS ON THE APPLICATION OF INDEPENDENT CURRICULUM FOR ELEMENTARY SCHOOL IN NATURAL SCIENCE SUBJECT - Anita Ekantini; Ika Damayanti (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract This study explored students' views on applying the independent curriculum in natural science subject. The method used was descriptive qualitative. The sample was fourth-grade students of Islamic Elementary School (IES) Salsabila Yogyakarta, selected using a purposive sampling technique. The instruments used were questionnaires and interviews. Data analysis used an interactive model, namely the reduction stages, data presentation, and conclusion. The findings of this study indicated that the fourth-grade students of IES Salsabila Yogyakarta responded positively to natural science learning, combined with social studies, to become Natural and Social Science (NSS). NSS gives students holistic knowledge so they get complete learning, hoping to make themselves individuals with a stand-in dealing with a problem. Therefore, it is expected that the application of the independent curriculum in natural science subject can be facilitated with media that support learning. Socialization or technical guidance for educators is needed in manufacturing innovative media to make this happen.